Geochronology and geochemistry of Late Triassic granitoids in Harizha Cu polymetallic deposit (East Kunlun Orogen) and their metallogenic constraints - Zhang, Wenzhao; Xia, Chulin; Zhen, Shikun; Quan, Chang’en; Du, Yu; Han, Zhihong (Frontiers in Earth Science, 2022)
The large Harizha copper (Cu) polymetallic deposit is located in the eastern section of East Kunlun Orogen. The ore-related lithologies include mainly the granodiorite, monzogranite, and their porphyries. Zircon U-Pb dating of the ore-bearing granodiorite porphyry and granite porphyry yielded Late Triassic age of 217 Ma. The rocks are characterized by being rich in SiO2 (68.44–78.13 wt%) and high alkali (4.03–8.33 wt%) and peraluminous (A/CNK = 1.02–1.68). In general, the granite samples are peraluminous and high-K calc-alkaline. The rocks are significantly enriched in light rare earth elements (LREE), large ion lithophile elements (e.g., K, Rb, Ba) and other incompatible elements (e.g., U, Th), but are depleted in heavy rare earth elements (HREEs), with weakly negative Eu and Ce anomalies, resembling I-S transitional granite. The zircons have εHf (t) = -8 to -4, and the corresponding zircon two-stage Hf model age (TDM2) from 1.5 to 1.8 Ga. We speculated that the ore-forming materials in the mining area were mainly from partial remelting of crustal materials, and that the tectonic regime was post-collisional extension.